EL TRATAMIENTO DE LAS UNIDADES FRASEOLÓGICAS EN EL TEXTO PERIÓDISTICO (Journal of the College of Languages (JCL), 2014)
The team of this investigation deals with phraseology and the importance of its organized use in the media of communication, especially in the daily newspaper which is used by different society classes. So, the journalist and news editors have to give a special importance for the phrasing, so as to, bring the attention of the readers. And expressing it with intelligence and accuracy, not only to give a special care for the decoration of phrases. So that news editors have to give importance for the using of linguistic connectors and correct use of punctuation marks, because of its influence in the right comprehension of phrases. The study is divided into five parts:- - The first contains, introduction its objects, in addition to the methodology which we use to realize this study. - The second expresses the theatrical parts. In this part we talk about the writers of phraseology. - The third contains our practical part which is an analytic study for two Spanish newspapers.- The fourth: Conclusion . - The fifth: bibliography.